A pilot study to assess bacterial and toxin reduction in patients with Clostridium difficile infection given fidaxomicin or vancomycin. Issue 1 (December 2016) - Thabit, Abrar; Alam, M.; Khaleduzzaman, Mohammed; Garey, Kevin; Nicolau, David
Abstract Background To assess the effect of fidaxomicin and vancomycin onClostridium difficile toxins and correlation with clinical and microbiologic outcomes. Methods Hospitalized patients withC. difficile infection were randomly assigned a 10-day course of fidaxomicin or vancomycin. Stool samples collected at baseline (day 0), mid-therapy (days 3–5), end of therapy (days 10–13) and follow-up (days 19–38) were assessed for quantity of toxins A and B as well as spore and vegetative cells counts. Correlation of toxins concentrations with microbiologic and clinical findings were evaluated. Results Among 34 patients 12 had detectable toxin concentrations at baseline seven were randomized to fidaxomicin and five to vancomycin. Overall both fidaxomicin and vancomycin resulted in drop of both toxins concentrations by midpoint of therapy. The drop in toxin A concentrations was maintained up to the follow-up period with fidaxomicin but not with vancomycin even in patients who developed recurrence. Patients who developed recurrence in the fidaxomicin group had lower concentrations of toxin B versus the recurrence patient of vancomycin group. Presence of vegetative cells and spores was significantly linked with high toxin A (P  = 0.003 and <0.001 respectively) and toxin B (P  = 0.007 and <0.001 respectively) concentrations across time points. Toxin B concentrations but not A significantly correlated with stool consistency (P  < 0.001) and frequency (P  = 0.05). Conclusions Fidaxomicin was associated with sustained reduction of both toxins up to 30 days post therapy versus vancomycin. Multiple clinical or microbiologic observations were correlated with toxin A or B concentrations.